Efeitos de história de punição sobre a emergência de relações entre estímulos - Bast, Diana Ferroni (2010)
This experiment examined the conditioned emotional functions after a experimental condition on the formation of stimulus equivalence relations. This study was composed by four phases and it has been initiated after six participants have completed the IDATE and BDI scales. Three favorite words had been chosen by participants in the first phase and they would be used at the end of experiment. The second phase consisted on the formation of stimulus equivalence of arbitrary stimuli and all participants have achieved the 90% criterion. After, Phase 3 was designed to stablish an operant response function for 3 stimuli of the previous phase that would acquire distincts functions: neutral, aversive (S-) and positive reinforcing stimuli (S+). Three participants showed conditioned suppression when submitted to the S-. Finally, in the Phase 4, new stimulus equivalence relations would be done with each stimuli used in the Phase 2 and new stimuli (arabic and positive words that had been choosen by participants). The results showed that, two participants could not reach the last criterion for the formation of stimulus equivalence relations and they required more testing trials in the MTS training blocks-to-criterion and equivalence testing for S-/S+ condition and S+/S+. These two participants were found in the group that demonstrated conditioned supperssion on Phase 3. The others participants required less repetitions and it was detected different patterns of mistake among them, probably related with the experimental history of Phase 3. The fact of the participants scored anxiety or depression in the scales utilized was not correlated with the main interfering effect but experimental history was. Implications of this study for treatment of clinical treatments are considered